2020
DOI: 10.1186/s12875-020-1078-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in assessing suspected bone fractures: a cross-sectional survey amongst German general practitioners

Abstract: Background: Over the last two decades, ultrasonography (US) has been shown to be an accurate tool for the diagnosis of suspected bone fractures; however, the integration of this application of US into routine care and outpatient settings needs to be explored. In this study, we surveyed German general practitioners (GPs) to assess their knowledge, attitudes, and utilization of US for the diagnosis of suspected fractures. Methods: Notification of the study, a self-designed questionnaire, and a reminder were mail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The majority of responders (71.9%, n =192/267) stated that the US was less successful than traditional XRs in diagnosing bone injuries. Despite the fact that 39.3% ( n =110/280) of clinicians were aware of this imaging technology, only 19.1% ( n =54/283) considered it important to their own practice, and only 7.8% ( n =22/282) had any practical e41%) experience using US to detect fractures 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of responders (71.9%, n =192/267) stated that the US was less successful than traditional XRs in diagnosing bone injuries. Despite the fact that 39.3% ( n =110/280) of clinicians were aware of this imaging technology, only 19.1% ( n =54/283) considered it important to their own practice, and only 7.8% ( n =22/282) had any practical e41%) experience using US to detect fractures 11 .…”
Section: Resultsmentioning
confidence: 99%
“…A study revealed only 39.3% of clinical practitioners in Germany were aware of the applications of US in fracture diagnosis and 71.9% believed US to be less efficient than XR. However, users of US were found to be well informed 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of radiation exposure is one of the primary benefits of ultrasonic testing; this is especially true in pregnant and children, who are more vulnerable to radiation than adults (10). Ultrasonography as a diagnostic tool in situations of suspected fractures may offer economic, prognostic, and therapeutic benefits, particularly in terms of reducing unnecessary radiation exposure to human body (11).…”
Section: Introductionmentioning
confidence: 99%